Pengaruh Karakteristik Wilayah dan Otonomi Perempuan terhadap Praktik Pemberian Makan Bayi dan Anak: The Effect of Regional Characteristics and Women's Autonomy on Infant and Young Child Feeding Practice - Putricia Synthesa; Djoni Hartono (Universitas Airlangga, 2023)
Background: Appropriate infant and young child feeding practices (IYCF) for children aged 6-23 months are vital for their growth and can prevent stunting. There is high variation between provinces regarding nutrition, which makes it essential to analyze based on contextual variables at the provincial level. Objective: Aimed to study the effect of contextual variables and women's autonomy variables and study the effects of the differences between these two variables on IYCF on the three leading indicators, namely MDD, MMF, and MAD. Methods: Used multilevel logistic regression analysis from the 2017 IDHS data with a research sample of 4,923 mothers who were married and lived with partners who had their last children aged 6-23 months. The dependent variable in this study was whether PMBA complied with WHO recommendations or not, which were divided into three groups: Minimum Meal Frequency, Minimum Dietary Diversity, and Drinkable Acceptable Diet. The independent variables were the independent variables at the individual level and the independent variables (contextual) at the provincial level. In addition, it will also be seen the influence of the interaction variables. Results: The results showed that the contextual variables associated with infant and child feeding practices were the percentage of poor people and the percentage of health facilities. Meanwhile, at the individual level, several indicators of the autonomy variable, along with the variables of mother's age, classification of residence, mother's access to the internet, age of children, and husband's education, have associations with IYCF in the three indicators used. The interaction variable showed a different effect on women's autonomy and contextual variables on IYCF. Conclusion: This study shows the results of regional characteristic variables, women's autonomy, and the interaction variables between the two can influence IYCF.